GUEST SATISFACTION WITH THE OFFER OF EUROPEAN INTERNATIONAL DISHES AND PRODUCTS IN SERBIAN RESTAURANTS - Vukolić, Dragan; Gajić, Tamara; Bugarčić, Jovan (The Business of Tourism, 2021)
Abstract: Tourism is one of the areas that has started to develop to a large extent in the last few years, and the expansion of gastronomy has also contributed to its development. Regardless of the area in question, the development of gastronomy and quality offer of food and beverages is one of the means, which ensures the quality of services in the catering facility. Some countries have protected their gastronomic products, and today certain dishes bear the title of international dish. This paper will present the results obtained after the research in 30 restaurants, with the aim of examining the satisfaction of guests with their offer of international dishes. Over the past years, the literature has become richer in numerous studies, which talk about the factors that affect the level of satisfaction with the gastronomic offer. By analyzing the obtained results, it was concluded that the guests of catering facilities in Serbia are largely satisfied with the offer of international dishes. A significant percentage of respondents, who are not satisfied with this offer, show that there is still a need to improve catering services, from which we must not omit the offer of international dishes. SPSS software version 23.00 was used to process the obtained data, and the data are presented with descriptive statistics.